Chromosome 5p Region SNPs Are Associated with Risk of NSCLC among Women. (26th January 2010) - Van Dyke, Alison L.; Cote, Michele L.; Wenzlaff, Angela S.; Abrams, Judith; Land, Susan; Iyer, Priyanka; Schwartz, Ann G.
Abstract : In a population-based case-control study, we explored the associations between 42 polymorphisms in seven genes in this region and non-small cell lung cancer (NSCLC) risk among Caucasian (364 cases; 380 controls) and African American (95 cases; 103 controls) women. Two TERT region SNPs, rs2075786 and rs2853677, conferred an increased risk of developing NSCLC, especially among African American women, and TERT -rs2735940 was associated with a decreased risk of lung cancer among African Americans. Five of the 20 GHR polymorphisms and SEPP1 -rs6413428 were associated with a marginally increased risk of NSCLC among Caucasians. Random forest analysis reinforced the importance of GHR among Caucasians and identified AMACR, TERT, and GHR among African Americans, which were also significant using gene-based risk scores. Smoking-SNP interactions were explored, and haplotypes in TERT and GHR associated with NSCLC risk were identified. The roles of TERT, GHR, AMACR and SEPP1 genes in lung carcinogenesis warrant further exploration.